Role of Ayurveda in the Management of Mukhapaka WSR to Oral Cancer – A Review - Pariksha, Armaan (International Research Journal of Ayurveda & Yoga, 2023)
Background: Mouth ulcers known as “Mukhpak” or “Sarvasar Rog” frequently occur. Its signs and symptoms are comparable to those of oral cancer. The term “oral cancer” refers to cancer that affects the lips, tongue, palate, gingiva, alveolar mucosa, buccal mucosa, and oropharynx. In India, oral cancer is distinct from oral cancer in Western countries because it is more likely to be caused by tobacco use (70%) and is more likely to be discovered in its third or fourth stages. The habit of chewing betel nuts and tobacco, consuming large amounts of chiles and other spices, having a weak immune system, smoking, drinking alcohol, and having dietary deficits are all likely to contribute to the disease. Materials and Methods: Both primary and secondary sources were used to gather the data for the current analysis, with literary studies of key Ayurvedic texts and Samhitas as well as commonly read research articles serving as particular examples. Results: The Ayurvedic analysis of the disease situation suggests that it is more closely related to chronic Sarvasara mukharoga, a Vata-pitta dominant syndrome. This trait of mouth cancer, according to Ayurveda, is present in Vata paitik people. Discussion: To cure this condition, some medication that is described in the Ayurvedic classics has been collected.